Study of the Properties and Particulate Matter Content of the Gas from the Innovative Pilot-Scale Gasification Installation with Integrated Ceramic Filter - Andrzej Sitka (MDPI AG, 2021)
This paper presents a study on the application of a ceramic filter in the biomass gasification process and its efficiency in particulate matter removal from the process gas and flue gas. A significant advantage of this type of filter is its high efficiency in small particle removal (<1 µm). This feature allows us to reach the much lower emissions that are required by the applicable standards. The study was performed using an original biomass gasification installation, where conifer scobs were used as feedstock. The installation, its operation and measurement methodology are described in the article. The study included the analysis of process gas and particulate matter, as well as particulate matter content before and after the filter was applied. The measurements indicate that the efficiency of particulate matter removal reaches 99.1%. The analysis of particulate matter in the process gas allowed us to determine that its content was 18.26%, and additionally it was indicated that it contained combustible parts, which undergo combustion in the combustion chamber. It was found that the content of particulate matter is reduced 11 times when compared to the process gas before the filter. An accurate estimation of particulate matter content in flue gas has been also shown for the system without the ceramic filter. As a result, the method allowed us to determine the overall efficiency of particulate matter removal using the ceramic filter, which is equal to 99.9% or 2 mg/m3 (N). The performed study shows that pre-combustion particulate matter removal is preferred over post-combustion particulate matter removal from flue gas. The reason is that the stream of process gas is several times smaller than the flue gas stream, thus the required size of the filter is smaller. Furthermore, process gas filtering allows us to keep the heat transfer surfaces clean, which preserves high thermal efficiency and durability of equipment. The presented results of performed tests are the early stage of the development of the technology of process gas refining in the waste gasification process. The final target is to reach standards similar to those in the case of natural gas.